Evidence on Integrating Pharmacokinetics to Find Truly Therapeutic Agent for Alzheimer’s Disease: Comparative Pharmacokinetics and Disposition Kinetics Profiles of Stereoisomers Isorhynchophylline and Rhynchophylline in Rats - Chunyuan Zhang (Evidence-Based Complementary and Alternative Medicine, 2019)
Isorhynchophylline (IRN) and rhynchophylline (RN), a pair of stereoisomers, are tetracyclic oxindole alkaloids isolated from Uncaria rhynchophylla, a commonly used Chinese medicinal herb. These two compounds have drawn extensive attention due to their potent neuroprotective effects with promising therapeutic potential for the treatment of Alzheimer’s disease (AD). However, IRN and RN can interconvert into each other in vivo after oral administration. The present study aimed to elucidate the pharmacokinetic profiles and disposition kinetics of the administered and generated stereoisomers in the brain and cerebrospinal fluid (CSF) after oral administration of equal dose of IRN or RN to rats. Our study demonstrated that after oral administration, RN showed significantly higher systemic exposure (6.5 folds of IRN, p < 0.001) and disposition in the brain (2.5 folds of IRN, p < 0.01) and CSF (3 folds of IRN, p < 0.001) than IRN. The results indicated that interconversion between IRN and RN occurred. Notably, regardless of the orally administered IRN or RN, RN would always be one of the major or predominant forms present in the body. Our results provided sound evidence supporting further development of RN as a potential therapeutic agent for the treatment of AD. Moreover, the present study sets a solid example that integrating pharmacokinetics is crucial to identify the truly therapeutic agent.